Volume 6C: Turbomachinery 2013
DOI: 10.1115/gt2013-95770
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Design and Analysis of Centrifugal Turbine Cascades

Abstract: The centrifugal turbine architecture represents a promising solution for Organic Rankine Cycle (ORC) Systems, in the small-to-medium power range. The large volumetric expansion ratios occurring in ORC turbines complicate the design of the turbo-expander, making the centrifugal arrangement worth of interest with respect to conventional architectures. A new-concept centrifugal turbine has been recently proposed by the authors, based on the design of Ljungström but implementing a stator-rotor arrangement, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 0 publications
3
26
0
Order By: Relevance
“…A mobile small- application market is currently ongoing [35] and it is receiving more analytical studies by [30,31,32]. While the detailed studies are conducted of radial-inflow turbine that combined with mean-line design and ORC cycle analysis and followed by three-dimensional CFD simulation for a number of working fluids and operating conditions as reported by Sauret et al [1,27,36] and other studies [2][3][4][5][6][7][8][9][10][11]15,17,21,22,26,29,33,34].…”
Section: Turbine Designmentioning
confidence: 99%
See 2 more Smart Citations
“…A mobile small- application market is currently ongoing [35] and it is receiving more analytical studies by [30,31,32]. While the detailed studies are conducted of radial-inflow turbine that combined with mean-line design and ORC cycle analysis and followed by three-dimensional CFD simulation for a number of working fluids and operating conditions as reported by Sauret et al [1,27,36] and other studies [2][3][4][5][6][7][8][9][10][11]15,17,21,22,26,29,33,34].…”
Section: Turbine Designmentioning
confidence: 99%
“…The pressure loss coefficient and enthalpy loss coefficient are approximately equal at a small value of enthalpy [39,41] has been used by many researchers working on radial-outflow turbines, such as [30,31,32,42]. This losses model only includes the profile loss and secondary loss [32].…”
Section: Mean-line Design Of Axial and Radial-outflow (Centrifugal) Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Persico et al [10] studied a design technique of a radial outflow turbine for a 1 MW organic Rankine cycle. The study found that the intrinsic diverging form of the radial outflow configuration makes the blade design difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Abroad, the preliminary hydrodynamic design of a small centrifugal turbine for the ORC was studied by Casati and others of the Delft University of Technology. They introduced the optimization based on the intermediate streamline method for evaluating turbine design and performance [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%